2017
DOI: 10.1159/000468527
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Neuropsychological Outcome after Stereotactic Radiofrequency Amygdalohippocampectomy for Mesial Temporal Lobe Epilepsy: Longitudinal Study

Abstract: Purpose: To assess the neuropsychological performance recoded over a period of 5 years after stereotactic radiofrequency amygdalohippocampectomy (SAHE) in the treatment of mesial temporal lobe epilepsy. Material and Methods: Thirty patients (mean age 38 years, 14 females/16 males) were included in this study. Twenty-one patients were treated on the left side, 9 on the right. Patients underwent neuropsychological evaluation by the Wechsler Adult Intelligence Scale-Revised and the Wechsler Memory Scale-Revised p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…In our 12 patients, SEEG was used not only for better localization of SOZ in patients with MTLE, but also for the RFTC approach as a further treatment for epilepsy. We found that seizures were mostly well controlled after RFTC (Engel I: 75% of patients), which was similar to the findings of previous studies ( Kramska et al, 2017 ; Malikova et al, 2014 ). The invasive EEG results and middle-term surgical outcomes were used as the gold standards to confirm the diagnosis and localization of MTLE.…”
Section: Discussionsupporting
confidence: 91%
“…In our 12 patients, SEEG was used not only for better localization of SOZ in patients with MTLE, but also for the RFTC approach as a further treatment for epilepsy. We found that seizures were mostly well controlled after RFTC (Engel I: 75% of patients), which was similar to the findings of previous studies ( Kramska et al, 2017 ; Malikova et al, 2014 ). The invasive EEG results and middle-term surgical outcomes were used as the gold standards to confirm the diagnosis and localization of MTLE.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with other results, a study of TLE patients over a 13 year period also showed no significant change in cognitive function ( 36 ). In addition, Helmstaedter and Elger ( 37 ) and Krámská et al ( 38 ) revealed, based on their longitudinal-sectional study of declarative cognitive functioning in chronic refractory partial epilepsy, that there was no deterioration in neuropsychological performance after a long period of epilepsy. The ANT scores are remarkably stable, with only a decline the orientation effect over time in our results.…”
Section: Discussionmentioning
confidence: 99%
“…24,26,28,47,48,57 Improved neurocognitive outcomes, however, could be offset by reductions in seizure freedom; thus, further evaluation of surgical targets is needed to optimize seizure and neuropsychological outcomes. 19,47,48,59 Future studies should consider more comprehensive testing, standardized metrics, and longer follow-up periods paired with QoL assessments to observe potential long-term impacts of cognitive impairment on individuals' lives.…”
Section: Neurocognitive Outcomesmentioning
confidence: 99%